Estimating sustainable biomass harvesting level for charcoal production to promote degraded woodlands recovery: A case study from Mutomo District, Kenya. (17th April 2018) - Ndegwa, Geoffrey M.; Nehren, Udo; Anhuf, Dieter; Iiyama, Miyuki
Abstract: Charcoal is an important urban fuel; however, when production is unregulated, it is a major cause of land and forest degradation. Production through selective harvesting of the preferred large, hardwood tree species leads to a degraded residual forest or woodland composed of juvenile hardwood trees and unused softwood tree species. This situation can be addressed by ensuring that the rate of preferred tree species extraction does not exceed the mean annual increment. This study estimated the sustainable rate of tree harvesting for charcoal in Mutomo District, based on field data collected between December 2012 and January 2013, through a forest inventory. The woodlands are subjected to selective logging for charcoal production, an activity undertaken by about half of the residents for their livelihood. The study findings show that charcoal production through selective logging has led to a reduction of the hardwood trees biomass density to 3.8 t ha −1 compared with an estimated desirable level of 12.5 t ha −1 . The results also show that it would take between 25 and 31 years for the woodlands to recover to the desirable stocking level if harvesting was completely stopped. This duration would increase to between 54 and 64 years if 80% of the mean annual increment was harvested for charcoal production and 20% was retained for woodlands recovery. As the residents of Mutomo District are poor and highly dependent on charcoal production for their livelihood, a harvesting plan based on the latter option would set the woodlands on the path to recovery and ensuring a sustainable livelihood source.